2021
DOI: 10.18494/sam.2021.3015
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparameter Optimization of Deep Learning Networks for Classification of Breast Histopathology Images

Abstract: After tumor detection in their breasts, women typically fear mastectomy; this affects curative care outcomes. Most tumors are benign. After resection and pathological examination, because of advances in medicine and treatment, the success rate of early breast cancer treatment can reach 60 to 90%. An accurate assessment of tumor extent is essential. In this study, a novel method of hyperparameter optimization of deep learning networks was proposed to classify tumors as malignant or benign. When setting hyperpar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…DL has been applied heavily to analyze tumor detection, grading, subtypes, predictions, etc [18]. Lin et al [19] acquired 77.50% accuracy using single-layer CNN. Darken et al [20] proposed a better LeNet-5 (RMSprop) method and achieved 82.58% accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…DL has been applied heavily to analyze tumor detection, grading, subtypes, predictions, etc [18]. Lin et al [19] acquired 77.50% accuracy using single-layer CNN. Darken et al [20] proposed a better LeNet-5 (RMSprop) method and achieved 82.58% accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Propose a new deep architecture based on self-integration to leverage semantic information from annotated images and explore information hidden in unlabeled data [140] Propose an analysis and synthesis model learning method with novel algorithms and search strategies to classify images more effectively [141][142][143][144][145][146][147][148][149][150] Propose a set of training techniques and use image processing techniques to improve the performance of CNN-based models in breast cancer classification [143,[151][152][153][154][155][156][157] Deep residual network (ResNet) Present a deep neural network which performs representation learning and cell nuclei recognition in an end-to-end manner [158] Propose an automatic multiclassification method for breast cancer histopathological images based on metastasis learning [159] Present a method that employs a convolutional neural network for detecting tumor on entire-slide images [59,130,136,160] Propose a breast cancer multiclassification method using a proposed deep learning model [106,113,137,[161][162][163][164][165][166][167][168] Thus, through research and analysis, we found that the classifier proposed by [110] first predicts the class label of each input patch by OPOD technique and then predicts the whole-image label by APOD technique. At the same time, the number o...…”
Section: Model Strategy Advantages Publicationmentioning
confidence: 99%
“…In recent years, computer-aided technologies have been widely adopted to achieve automated inspection for health care delivery, having a wide range of applications from scalp inspection (1) to lung nodule detection (2) in radiology and lesion classification (3) in histopathology. However, biomedical image analysis is a complex task that relies on highly skilled domain experts, such as radiologists and pathologists.…”
Section: Introductionmentioning
confidence: 99%